The study of refractrive index change in the chamber using mach-zehnder interferometer - 409978 Siti Norfaezah Kosenin; Yusof Munajat, supervisor; Fakulti Sains (2008)
Project Paper (Sarjana Muda Sains (Fizik Industri)) - Universiti Teknologi Malaysia, 2008